2022
DOI: 10.3390/ijerph19042436
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Gambling Associated with Impulsivity among a Swedish University Sample

Abstract: Excessive alcohol use and gambling can have negative consequences. Across countries, the risk of excessive alcohol use is more common in university populations than in the general population. However, few studies have investigated the prevalence of both alcohol use and gambling in this group. This study explores these behaviours in a Swedish university setting. In addition, this study investigates how impulsivity affects alcohol use and gambling. In total, 794 Swedish students answered an online survey. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…A multinomial logistic regression was conducted with PGSI (three categories) with sociodemographic variables, socioeconomic cluster, neighborhood cohesion, depression, anxiety, stress, gambling behaviors score, and legal and illegal gambling indicators as predictors. Note that PGSI is an ordinal variable, which usually implies an ordinal logistic regression, but since it failed to meet assumptions for proportional odds, a multinomial logistic regression was used, similar to previous studies that have administered the PGSI ( 41 , 44–46 ). The independent ordinal variables (socioeconomic cluster, neighborhood cohesion, stress, and gambling behaviors score) were standardized prior to being included in the regression analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multinomial logistic regression was conducted with PGSI (three categories) with sociodemographic variables, socioeconomic cluster, neighborhood cohesion, depression, anxiety, stress, gambling behaviors score, and legal and illegal gambling indicators as predictors. Note that PGSI is an ordinal variable, which usually implies an ordinal logistic regression, but since it failed to meet assumptions for proportional odds, a multinomial logistic regression was used, similar to previous studies that have administered the PGSI ( 41 , 44–46 ). The independent ordinal variables (socioeconomic cluster, neighborhood cohesion, stress, and gambling behaviors score) were standardized prior to being included in the regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Participants are classified into four severity categories: 0 = 'Non-problem gamblers'; 1-2 = 'Low-risk gamblers'; 3-7 = 'Moderaterisk gamblers'; and 8+ = 'Problem gamblers' . Note that previous epidemiological studies have merged 'moderate-risk gamblers' and 'problem gamblers' into one category (38)(39)(40)(41). The Cronbach's alpha for this scale was 0.832 for the Israeli Jewish respondents and 0.696 for the Israeli Arab respondents.…”
Section: Problem Gambling Severity Indexmentioning
confidence: 98%
“…Specific sociodemographic factors were identified across numerous studies and include a mix of risk and protective factors such as increased educational attainment [106][107][108][109][110][111], relative deprivation [112][113][114], parental engagement and role modelling [115][116][117][118][119][120][121][122][123][124], peer group behaviour [125], and location of residence relative to numbers of gambling venues [126,127]. Coincidental substance use and/or abuse was also identified as a strong risk factor for gambling, both in terms of frequency and severity (amount of money lost per event) [128][129][130][131][132][133][134], along with increased diversity of gambling product use and frequency [135][136][137][138][139]. The normalisation of gambling and/or sports betting was also explicitly described as a risk factor in gambling activities in pre-teens.…”
Section: Overviewmentioning
confidence: 99%
“…2 Alcohol exposure can have a widespread impact on the physical and mental health of young adults. Studies have shown that alcohol exposure in young adults increased the risk of gambling, 3 smoking, 4 drug use, 5 and violence. 6 At the same time, it can also increase the risk of cardiovascular diseases, 7 digestive diseases, 8 cancers, 9 and other diseases 10 in later life.…”
Section: Introductionmentioning
confidence: 99%